Optimizing Employee Transfer in an Effort to Get Acceptable Employees at the Directorate General of Defense Forces - Cecep Usman Akbar Askanta; Fibria Indriati (Publikasi Indonesia, 2024)
This research aims to examine the employee transfer system in order to obtain adequate competence at the Directorate General of Defense Strengthening. The method used is a qualitative approach with literature studies and in-depth interviews with employees within the Directorate General of Customs and Defense. The results of the study show that the current employee transfer process has not adopted the merit system optimally, with the existence of dominant administrative filing and lack of transparency and accountability. In addition, there are shortcomings in the assessment of performance and competencies from previous workplaces, as well as orientation and training programs that have not been fully effective. These findings underscore the importance of reforms in human resource management in the public sector to improve employee competence and performance. It is hoped that the implementation of the merit system, competency-based assessment, and improvement of training programs can overcome existing problems and optimize organizational performance.